THE ROLE OF SURGERY IN HOMOZYGOUS Î²-THALASSAEMIA - Muhammad, Gul; Gandapur, Abdul Salam Khan; Khan, Darya; Tayyab, Muhammad; Khan, Misal (Journal of Ayub Medical College Abbottabad, 2000)
Background: Various Strategies are adopted for the control and management of thalassaemia. Despite advances in the medical management of thalassaemia there remains a definite place for splenectomy in the management of thalassaemia, particularly in a developing country like Pakistan. Methods: The Surgical aspects of the management of patients with homozygous (3-thalassaemia are reviewed, and operative findings in 15 patients with the disease who were subjected to splenectomy are described. Results: Post-operatively frequency of blood transfusion was reduced for maintaining the haemoglobin level, due to decreased blood consumption. The age range was from 12-13 years. Hepatomegaly was present in all the cases. In 73 percent cases hyperplastic lymph nodes containing erythropoietic elements were found. Cholelithiasis was seen in only one case. The recovery' was smooth in 10 (67%) cases. Wound infection developed in 2 cases. Pneumonia occurred in only one case. Two patients developed fever and one items which responded to conservative treatment.